MULTI-COUNTRY SURVEY FOR THE TEACHING AND LEARNING PROCESS OF ICT LITERACY IN SECONDARY SCHOOLS - Genci Berati (European Scientific Journal, ESJ, 2014)
This paper presents results of a survey in different countries around the world, concerning teaching and learning process of Information and Communication Technology in secondary schools. A quality and quantity description and evaluation is carried out for 35 countries around the world. We have compared and classified those countries based on their performance in Economical and political stability, ICT National Curricular aspects, in ICT Infrastructure, Aspects of literature, in Methodologies of ICT teaching and learning and in terms of teacher competencies and training. All the aspects mentioned are considered as key factors. A process of analyzing this data is carried out in order to figure out the importance and real impact of each key factor in the process of teaching and learning ICT subjects, with the focus in lower secondary schools.